2021
DOI: 10.1371/journal.pone.0258580
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey of asymptomatic malaria in Dak Nong province in the Central Highlands of Vietnam for the malaria elimination roadmap

Abstract: Asymptomatic parasite carriers represent a “silent” infective reservoir for malaria transmission and contributes to malaria persistence. However, limited data are available on asymptomatic malaria in Vietnam. Between November 2018 and March 2019, we conducted a malaria epidemiological survey of asymptomatic people (children ≥ 10 years old and adults ≥18 years old, n = 2,809) residing in three communes in Tuy Duc district, Dak Nong province in the Central Highlands of Vietnam. Based on the national stratificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…Our results were higher than those reported elsewhere in Africa and Asia; 2.8 -9.5% for mother-to-child transmissions in Burkina Faso [44], 2.6% asymptomatic malaria amongst Dak Nong children in Vietnam [56], 3.9 -8.7%% among Sherkole refugee camp and Wogera district U5C in Ethiopia [15,57], 5.2% reported in Thailand-Myanmar [22], 6.4% among U5C in endemic prone Marani -Western Kenya [48], and 6.8% reported among school children in Northwest Ethiopia [43].…”
Section: Prevalence Of Malaria/anaemia In Association With General Ch...contrasting
confidence: 90%
“…Our results were higher than those reported elsewhere in Africa and Asia; 2.8 -9.5% for mother-to-child transmissions in Burkina Faso [44], 2.6% asymptomatic malaria amongst Dak Nong children in Vietnam [56], 3.9 -8.7%% among Sherkole refugee camp and Wogera district U5C in Ethiopia [15,57], 5.2% reported in Thailand-Myanmar [22], 6.4% among U5C in endemic prone Marani -Western Kenya [48], and 6.8% reported among school children in Northwest Ethiopia [43].…”
Section: Prevalence Of Malaria/anaemia In Association With General Ch...contrasting
confidence: 90%
“…Recent studies in areas with high and low malaria transmission rates have revealed that asymptomatic infections contribute to malaria transmission. 53 Furthermore, asymptomatic malaria may precede symptomatic disease, and may confer partial immunity against infection. 54 In this study, participants were sampled at a single point in time.…”
Section: Discussionmentioning
confidence: 99%
“…High bed net coverage, however, does not necessarily equate with effective use, and the sub-optimal use of freely distributed bed nets has been reported in different settings, particularly among ethnic minority populations [ 15 , 16 ]. In Vietnam, the main risk groups for malaria are ethnic minorities and migrant workers whose varied demographic characteristics, forest work and mobility have been a challenge for standardized vector control interventions [ 17 22 ]. This paper reports the results of a mixed-methods study assessing factors limiting the uptake of ITNs in an ethnic minority setting in a remote forested area of Central Vietnam.…”
Section: Introductionmentioning
confidence: 99%